2022
DOI: 10.9734/arja/2022/v15i430167
|View full text |Cite
|
Sign up to set email alerts
|

Carrot Productivity under Various Levels of Irrigation and Fertilization

Abstract: Carrot (Daucus carota L.) is normally grown under irrigation system. In Tanzania, carrot productivity is still low, mainly due to poor agronomic practices as a result of limited information on optimal levels of irrigation water that enhance crop production. Thus, a study was conducted to evaluate the interactions between various irrigation levels under drip irrigation and soil-based NPK fertilizer for optimal growth, yield, and sugar content of carrots in Morogoro, Tanzania. The crop water requirement was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…From this, it can be observed that supplementary irrigation has little or no effect on plant height. Similarly, SAS [33], also pointed out this; according to him, plant heights were not significantly different (p>0:05) between the 80% and 100% water application levels. A similar experiment conducted on vegetable crop/potato showed that there was no statistically significant difference between treatments on plant height of potato, potato′s plant height was not affected by the rate of supplementary irrigation [34].…”
Section: Effect Of Different Supplementary Irrigation On Thementioning
confidence: 78%
“…From this, it can be observed that supplementary irrigation has little or no effect on plant height. Similarly, SAS [33], also pointed out this; according to him, plant heights were not significantly different (p>0:05) between the 80% and 100% water application levels. A similar experiment conducted on vegetable crop/potato showed that there was no statistically significant difference between treatments on plant height of potato, potato′s plant height was not affected by the rate of supplementary irrigation [34].…”
Section: Effect Of Different Supplementary Irrigation On Thementioning
confidence: 78%
“…It can be prepared as a salad, a cooked vegetable for recipes including soups, stews, and curries, as well as pickles, preserves, and desserts. [4]. In spite of the crop's many virtues, growing consumer demand, and the fact that it is a profitable crop, carrot production in Bangladesh is currently limited in scale and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…"The leading mango-growing states in India encompass Andhra Pradesh, Bihar, Gujarat, Uttar Pradesh, Maharashtra, Karnataka, Kerala, Tamil Nadu, Orissa and West Bengal. In Gujarat alone, mangoes are cultivated across a total area of 1,66,358 hectares, with a production of 1,22,2291 MT" [3,4,5,6]. "The cultivation is predominantly concentrated in districts like Valsad, Navsari, Surat, Bharuch, Rajkot, Jamnagar, Kutch and Junagadh, benefiting from the favorable agro-climatic conditions prevalent in these areas".…”
Section: Introductionmentioning
confidence: 99%